PERAN HUMAS DALAM MENSOSIALISASIKAN SEKOLAH SLB E NEGERI PEMBINA MEDAN DALAM MENJALIN HUBUNGAN DENGAN KELUARGA ANAK PENYANDANG DOWN SYNDROME MELALUI MEDIA JURNALISTIK - Risa Fadila; M Yoserizal Saragih (Jurnal Ilmiah Global Education, 2023)
This qualitative research analyzes the role of public relations in socializing SLB E Negeri Pembina Medan school in establishing relationships with families of children with downsyndrome through journalistic media, this research aims to find out and describe how the role of public relations in socializing SLB E Negeri Pembina Medan school in establishing relationships with parents and the community. Data collection techniques used in this study are observation and interviews used for data collection, parents who have downsyndome children are often ostracized in the community so that there are still many parents who have downsyndrome children who are less socialized in the community.